Peran Romantic Adult Attachment Terhadap Distres Psikologis Ibu Hamil Perspektif Islam: Studi Literatur Review - Mutia Nur Az Zahra; Karimulloh Karimulloh (Ulumuddin: Jurnal Ilmu-ilmu Keislaman, 2026)
This study aims to examine the role of romantic adult attachment  in the psychological distress of pregnant women from an Islamic perspective. This is considering that there has not been a specific discussion of this role in Islam. Meanwhile, in psychology, psychological distress is known to have a negative impact on pregnant women, and one of the factors is the lack of attachment of the partner (husband) as a place of dependence that provides a sense of security (romantic adult attachment ). The approach used in this study is qualitative with the literature review method. The results of the study show that the psychological distress felt by pregnant women is interpreted by a test from Allah SWT. While the exam is a form of reminder for individuals to carry out worship to Allah SWT. Therefore, harmonious relationships such as paying attention to each other in the marriage bond are included in worship, and can reduce psychological distress for pregnant women.